2014
DOI: 10.1111/aej.12097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethylenediaminetetraacetic acid gel on the incidence of dentinal cracks caused by three novel nickel‐titanium systems

Abstract: The aim of this study is to evaluate the incidence of crack formation while using Reciproc, WaveOne and Twisted File Adaptive with and without ethylenediaminetetraacetic acid (EDTA) gel. Seventy extracted mandibular premolars were included. The teeth were decoronated until roots of 16 mm were obtained. Samples were distributed into seven groups: group 1, no canal preparation (control); other groups were instrumented so; group 2, Reciproc; group 3, Reciproc + EDTA; group 4, WaveOne; group 5, WaveOne + EDTA; gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…A plethora of methodological approaches has been used to assess the effects of different endodontic procedures on dentinal crack formation, including endoscopy (95), infrared thermography (96), microcomputed tomography with (46,97) and without (45) contrast agents, stereomicroscopy (17,19,31,95,98), optical coherence tomography (41), scanning electron microscopy (26,50,(99)(100)(101)(102)(103), sectioning (12,13,18,(20)(21)(22)(23)(24)(25)(27)(28)(29)(30)(32)(33)(34)(35)52,53,61,104), synchrotron (40), transillumination (105), and transmission electron microscopy (102) ( Table 3). It is beyond doubt that these techniques have shown potential for endodontic research and have been used successfully over many years; however, some of them may provide questionable data.…”
Section: Critical Appraisal Of the Methods For The Assessment Of Dentmentioning
confidence: 99%
See 2 more Smart Citations
“…A plethora of methodological approaches has been used to assess the effects of different endodontic procedures on dentinal crack formation, including endoscopy (95), infrared thermography (96), microcomputed tomography with (46,97) and without (45) contrast agents, stereomicroscopy (17,19,31,95,98), optical coherence tomography (41), scanning electron microscopy (26,50,(99)(100)(101)(102)(103), sectioning (12,13,18,(20)(21)(22)(23)(24)(25)(27)(28)(29)(30)(32)(33)(34)(35)52,53,61,104), synchrotron (40), transillumination (105), and transmission electron microscopy (102) ( Table 3). It is beyond doubt that these techniques have shown potential for endodontic research and have been used successfully over many years; however, some of them may provide questionable data.…”
Section: Critical Appraisal Of the Methods For The Assessment Of Dentmentioning
confidence: 99%
“…According to these authors, preparation using only a single large‐tapered reciprocating instrument, which cuts substantial amounts of dentin in a short time, tends to cause or aggravate more dentinal defects than conventional preparation, which comprises a more progressive and slower mechanical enlargement. While some studies have found no difference regarding the kinematics of different systems on crack formation , most of them agreed that rotary instruments produce significantly more cracks than reciprocating instruments . It may be important to point out that among all preparation systems, ProTaper instruments have been frequently associated with the highest amount of crack initiation .…”
Section: Current Knowledgementioning
confidence: 98%
See 1 more Smart Citation
“…Alireza 38 and Aydin 39 reported similar results. Although RC-Prep acts as a lubricant during canal preparation, the wax-like smear layer caused by RC-Prep 28 may be thick and contain dentinal debris, and thus may increase the incidence of dentinal cracks.…”
Section: Crack Formationmentioning
confidence: 55%
“…Aydın ve ark.nın çalışmasında; Reciproc (VDW), WaveOne (Dentsply Maillefer) ve TFA sistemlerinin dentin defekt oluşturma insidansları mandibuler premolar dişlerde kesit alma yönte-mine göre incelenmiştir. 21 Araştırmacılar, test edilen üç farkı NiTi eğe sisteminin aralarında dentin defekti oluşturma bakımından istatistiksel olarak fark olmadığını bildirmişlerdir. NiTi eğelerin sahip olduğu hareket kinematiği, eğelerin kök kanal şe-killendirmesi sırasında oluşturduğu dentin defekti miktarını etkilemektedir.…”
Section: Discussionunclassified